"Meniscal extrusion in ultrasound as a new diagnostic tool for evaluation of medial meniscus function". Issue 4 (27th April 2017) - Diermeier, Theresa; Achtnich, Andrea; Imhoff, Andreas B; Wörtler, Klaus; Petersen, Wolf
Aims and Objectives: : In MRI meniscal extrusion is normally described as pathologic finding and associated with a loss of function of the affected meniscus. We hypothesize that in healthy knees there is also physiological meniscal extrusion as a functional adjustment on various load bearing conditions. Therefore meniscal extrusion is described as the difference in extrusion between standing and lying position in ultrasound as a new diagnostic tool to evaluate the function of a meniscus. Materials and Methods: : We analysed voluntary test persons with non-symptomatic knee, no further malalignment and without any operation to the knee in the past. At the beginning each patient was clinical examined to exclude ligament instability and afterwards the extrusion of the medial meniscus was measured in ultrasound in standing, with 20° of flexion, and lying position. To compare these measurments with the current gold standard every patient also got an MRI examination from the knee. Medial meniscus extrusion was defined as the distance between external boundry of medial tibial plate and the external base of the pars intermedia of medial meniscus Results: : At this time, 62 patients meet the inclusion criteria. In group I (25 persons, age 18-30 years) the average extrusion in lying position was 0, 5 mm and 1, 1 mm with full weight bearing. In group II (25 persons, age 31-50 years) the median extrusion in lying position was 1, 1 mm and 1, 8 mm with full weight bearing. In group III (25 persons, >50 years) the extrusion in lying position was 1, 4 mm and 2, 1 with full weight bearing. The determined meniscus extrusion of the medial meniscus in 62 healthy knees was 0.8 mm in the dynamic ultrasound examination. Conclusion: : Based on our results, there is a physiological functional medial meniscal extrusion in healthy knees as an adjustment reaction on various loadbearing conditions. Although the absolute meniscus extrusion is elevated in elderly people, the adjustment is similar compared to the younger groups. In contrast to MRI scans, ultrasound examination allows a dynamic examination of the meniscus with various load bearing conditions. Therefore ultrasound examination of the meniscus represents a useful tool to proof the function of a meniscus.